Perpanjangan Usia Tikus Tua Setelah Xenotransplantasi Human Umbilical Cord Mesenchymal Stem Cells (hUC-MSCs) - Tarigan, Elpita; Dwijayanti, Adisti; Suyatna, Frans Dhyanagiri; Bachtiar, Indra; Qlintang, Sandy; Adnyane, I Ketut Mudite; Boediono, Arief (Jurnal Veteriner, 2020)
Currently, mesenchymal stem cells (MSCs) for implementing regenerative medicine in aging become interest in medical research science, especially in degerative disease and other aging problems. This research was aimed to determine the effectiveness of hUC-MSCs on inhibiting the aging process through the lifetime of the rat and the effect of intravenous administration of hUC-MSCs in phisiologycally aging female rat on the blood analysis. This study was used 40 aged female rats with 29-30 months of age divided into four groups with 10 rats each. The control rat group was given physiological NaCl (0.9%) 0.5 mL, and the treated rat group was given hUC-MSCs 1x10 7 cells/kg body weight in 0.5 mL NaCl 0.9%, was injected intravenously in caudo lateralis tail vein with stratified frequency; one time injection (SC1), three times injections (SC3) and five times injections (SC5). Perifer blood was collected from retro-ortbital sinus vein 30 days before and after injection of hUC-MSCs for hematology and blood chemistry analysis. Based on the results were obtained, it indicated that hUC-MSCs increased the survival of aging rat were in treatment group, life span of rats was extended up to 40 months compared to the average life of control rat aged up to 34±2 months. The injection of hUC-MSCs 1x10 7 cells/kg of body weight with one, three and five times injection were affected to blood profiles and blood chemistry with correlation were low. The conclusions are hUC-MSCs extend the lifespan of aging rat and were affect the blood in general but in normal range of aging rat, affect in ALT and creatinin as tissue repair and tolerated by aging rat.